Governmental control of the Internet and WikiLeaks: How does the press in four countries discuss freedom of expression?. (August 2016) - Imre, Iveta; Pjesivac, Ivanka; Luther, Catherine A.
This study looked at how newspapers operating in nations with varying degrees of governmental Internet control discussed Internet freedom of expression within their coverage of Wikileaks. This was done through a thematic analysis of news items about WikiLeaks and Internet freedom of expression in the left-leaning newspapers of The Guardian (Great Britain), Le Monde (France), The Sydney Morning Herald (Australia), and The China Daily (China). The analysis revealed that government stances regarding Internet control did not shape the newspapers' discussion about WikiLeaks and freedom of expression on the Internet. Although governments in these countries exercise different levels of Internet control, the newspapers had similar positions about freedom of expression on the Internet and the role of the United States in censoring it. They supported Internet freedom as well as the actions of WikiLeaks and Julian Assange while criticizing U.S. attempts to suppress the online organization and its founder.